Healthcare professional and professional stakeholders' perspectives on vaccine mandates in Switzerland: A mixed-methods study. Issue 51 (5th December 2022) - Dietrich, Léna G.; Lüthy, Alyssa; Lucas Ramanathan, Pia; Baldesberger, Nadja; Buhl, Andrea; Schmid Thurneysen, Lisa; Hug, Lisa C.; Suzanne Suggs, L.; Speranza, Camilla; Huber, Benedikt M.; Tarr, Philip E.; Deml, Michael J.
Highlights: Swiss healthcare professionals are generally opposed to vaccine mandates. Swiss federal health authorities have clearly stated that vaccination is voluntary. Swiss healthcare professionals expressed concerns about COVID-19 vaccine mandates. Consequences of vaccine mandates for HCPs are currently unclear in Switzerland. Vaccination policy in Switzerland should be clarified for healthcare professionals. Abstract: Background: There currently are no mandatory vaccines in Switzerland. However, Swiss federal legislation allows for vaccination mandates in settings where the risk of transmission to vulnerable groups is high, such as healthcare professionals (HCPs) working with vulnerable patients. Since HCPs are trusted information sources, a priority population for COVID-19 vaccination, and potentially subjected to mandates, we investigated HCP perspectives on mandates. Methods: A national online survey was administered to HCPs (October 2020-March 2021), including vaccine mandates questions concerning patients (measles) and HCPs (influenza). We qualitatively investigated HCP mandate perspectives through: (1) 34 interviews with HCPs, HCP professional society representatives, and health authorities; (2) a focus group discussion (FGD) with complementary medicine (CM) and biomedical physicians, and Swiss Federal Vaccination Commission members. Results: 1933 participants (496 physicians, 226 pharmacists, 607 nurses, 604 midwives) responded to the survey. Quantitative results show all professional groups preferred shared parent-HCP measles vaccine decisions (65%, 54%, 50%, 48%, respectively; p for trend < 0.001). Midwives (87%) and nurses (70%) preferred individual influenza vaccination decisions for HCPs, while physicians (49%) and pharmacists (44%) preferred shared employee-employer decisions (p for trend < 0.001). Physicians (p < .001) and pharmacists (p < .01) with CM training favored individual influenza vaccination decisions. Qualitative results show general HCP opposition to vaccine mandates, mainly because participants argued how other approaches, such as HCP training and better information, could encourage uptake. Arguments against COVID-19 mandates included insufficiently documented long-term safety/efficacy data. From participants' perspectives, mandated vaccination should be used as a last resort. Some participants expressed fear that with mandates, notably for influenza and COVID-19, some HCPs might leave their jobs. HCPs were unsure what vaccine mandates would concretely look like in practice, particularly regarding sanctions for non-compliance and enforcement. Conclusion: In Switzerland, HCPs generally were opposed to vaccination mandates. Clarity and guidance are needed from health authorities to better inform discussions around vaccine mandates.